In vitro and In silico Antigout arthritic activities of Ethanolic and Aqueous stem extracts of Cissus quadrangularis - A TLR2 and TLR4 Receptor approach - Tharini Palani, Krishnan Shobha, Thirunavukkarasu P, Rajeswary Hari (Journal of Applied Pharmaceutical Science, 2018)
The in vitro anti-gouty arthritic activity of ethanolic and aqueous extracts of Cissus quadrangularis stem was evaluated in terms of inhibition of xanthine oxidase, proteinase enzyme, protein denaturation and membrane stabilization. The Monosodium Urate (MSU) up-regulated expression patterns of toll-like receptors namely TLR-2 and TLR-4 were analyzed. The molecular docking was performed to select the antagonistic phyto ligand for receptors since their activation leads to the destructive immunological reactions occurring in gouty arthritis. The in vitro anti-gout arthritic activities were estimated using standard protocols. The MSU crystal-induced toll-like receptors gene expression was analyzed. Molecular docking and LIGPLOT analysis were performed with the GCMS-derived phytoconstituents in the ethanolic extract of Cissus quadrangularis with the receptors to find the interactions. Colchicine was used as a positive drug in the study. Among the two extracts, ethanolic extract revealed better in-vitro anti-arthritic activity in the present investigation. Out of the GCMS derived 13 phytocomponents, based on docking score three main components namely Pentadecanoic acid, 14-methyl,-methyl ester, 10-Octadecenoic acid, methyl ester, 4-one,2-(3,4- dihydroxyphenyl)-2,3-dihydro-3,5,7-trihydroxy showed better antagonistic action in the LIGPLOT analysis. It may be concluded these three ligands may further develop as a potential anti-gouty arthritic drug.
Keywords: Anti gout, Monosodiumurate, Toll-like receptor,Xanthine oxidase.